Landscapes and forest flora of al-Andalus: a reconstruction from textual historical documentation - Hernández Bermejo, J. Esteban; Carabaza Bravo, Julia Mª; García Sánchez, Expiración; Herrera Molina, Francisca (Mediterranean Botany, 2019)
The translation and interpretation of works by Andalusi botanists and agronomists provide an increasingly sharp image of the species and forest landscapes in al-Andalus (Iberian area under Muslim rule in the Middle Ages). Regarding agriculture, it is known that domestication processes and the introduction of new species and singular forms of use were carried out, thus changing agricultural landscapes. Consequently, new life styles and consumption habits developed. A lot less is known about forestry management, especially when referring to forest landscapes and tree species in the Iberian Peninsula. The authors of this work have been studying agricultural and forest flora in al-Andalus for many years. In addition to numerous miscellaneous contributions, their first approximation on the trees and shrubs cultivated there was published in 2004, and the first volume of Flora Agrícola y Forestal de Al-Andalus covering 80 species of monocotyledons appeared in 2012. In anticipation of the volume devoted to woody dicotyledons to be published in 2019 (including over 150 species, 100 genera and 50 families), a synthesis of the forest landscapes and the most unique species in the Arabic texts is presented in this work. Among the taxa identified are Iberian endemics such as Flueggea tinctoria and Corema album, rare taxa or highly localized ones like Rhododendron ponticum subsp. baeticum, Tetraclinis articulata and Zizyphus lotus with species of peculiar forestry interest such as Arctostaphylos uva-ursi, Taxus baccata, Buxus sempervirens, Ilex aquifolium, Laurus nobilis and Vitex agnus-castus, and archaeophytes like Celtis australis or Anagyris foetida.